SYNESTHESIA BETWEEN SOUND AND COLOUR - George APOSTOLESCU (Studia Universitatis Babeş-Bolyai. Musica)
Synesthesia is a syndrome or better said a psychological state that became manifest in music, art and literature. Mainly in the 20th century it takes a different shape as a result of scientific progress and especially of the effects it has generated. Synesthesia in music is recognized due to the effects created by Alexander Scriabin in Prometheus – The Poem of Fire as well as ”the painting” on the score of Hartmann’s pictures in his famous work Pictures at an Exhibition by Modest Mussorgsky. At the opposite pole we come across synesthetic episodes in pop-rock music or in disco dance music. The Avant-garde is a decisive factor of synesthetic development due to the synergy between music and visual art. The appearance and diversification of synesthesia creates new effects that influence all the people who interact with music and colours directly or indirectly.